In-situ and ex-situ comparison of the electrochemical oxidation of SO2 on carbon supported Pt and Au catalysts. (13th January 2020) - Meekins, Benjamin H.; Thompson, Anthony B.; Gopal, Varsha; Mehrabadi, Bahareh A.Tavakoli; Elvington, Mark C.; Ganesan, Prabhu; Newhouse-Illige, Ty A.; Shepard, Adam W.; Scipioni, Lawrence E.; Greer, James A.; Weiss, John C.; Weidner, John W.; et al.
Abstract: Electrochemical characterizations are performed using thin films and commercial carbon supported platinum and gold catalysts for sulfur dioxide oxidation, the primary electrochemical oxidation reaction in the Hybrid-sulfur (HyS) thermochemical process. Electrochemical evaluation of metal thin films qualitatively confirms the higher activity of Au over Pt, AuPt, Pd, and Ir for the electrochemical oxidation of SO2 . Ex-situ testing, using rotating disk electrode (RDE), shows an earlier onset potential for Au/C at low sulfuric acid concentrations (C ≤ 3.5 M) and a higher turnover frequency than Pt/C at sulfuric acid concentrations ranging from 3.5 M to 9 M. In-situ electrolysis experiments using low catalyst loadings (0.1 mgAu cm −2, a factor of ≥5 lower than typical loadings) confirm that Au nanoparticles exhibit higher current densities and greater stability than Pt nanoparticles. This is consistent with the thin film screening studies, which showed higher activity with increasing gold content in AuPt thin films. This work reveals an alternative material to state-of-the-art Pt to lower the energy needs and aid the HyS cycle in reaching the target of $2/kg H2 set forth by the Department of Energy to achieve economic feasibility of large-scale hydrogen generation. Graphical abstract: Image 1 Highlights: Au is more active and stable than Pt, AuPt, Pd, and Ir for electro-oxidation of SO2 . Electrolyzer experimental results confirm ex-situ electrochemical observations. Au provides a pathway to new catalysts that can meet projected performance targets.